Impact assessment of current knowledge gaps and mitigation strategies in clinical FLASH proton therapy through a systematic review - zur Horst, Anne H.; Habraken, Steven J. M.; Rovituso, Marta; Klaver, Yvonne L. B.; Spruijt, Kees H.; Hoogeman, Mischa S. (Frontiers in Oncology, 2025)
IntroductionFollowing first clinical trials, the development of FLASH proton therapy (FLASH-PT) into a mature treatment modality is ongoing, while physical and biological conditions underlying the FLASH effect remain uncertain. Our aim is to assess the impact of these uncertainties on clinical FLASH-PT through a novel approach.MethodsA systematic literature review was conducted to collect relevant in vivo preclinical studies as well as FLASH-PT treatment planning and delivery approaches. This information was used to perform an impact assessment: the FLASH-PT process from patient selection to treatment delivery was divided into steps, and seven FLASH conditions were defined. The FLASH conditions included physical, delivery-related, and radiobiological aspects. For each step and FLASH condition, scores were assigned based on the (i) criticality for clinical applications, (ii) current knowledge, and (iii) available mitigation strategies. These scores were combined to obtain an overall impact for all FLASH conditions ranging from insignificant impact not affecting clinical routine to severe impact causing severe complications for clinical translation.ResultsIn total, 14 preclinical and 27 treatment planning studies were identified. From these, 47 combined scores were reported in the impact assessment. A severe impact was found for patient selection in the context of radiobiological uncertainties for the robustness of the FLASH effect with respect to beam pauses and interruptions and for the evaluation of dose rate due to their importance in the treatment process combined with remaining unknowns. Moderate to insignificant impact was found for fractionation and FLASH-PT treatment delivery mode (transmission or Bragg peak beams), as these offer strategies to circumvent uncertainties. Overall, dose requirements, the use of multiple fields, and dose rate conditions emerged as the most crucial factors.ConclusionsSince uncertainties about the FLASH conditions hinder the utilization of its full pre-clinical potential in clinical practice, focusing future preclinical experiments to gain further phenomenological rather than only mechanistic insights on these aspects is recommended.